If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 4x + 9x Combine like terms: 4x + 9x = 13x 6 = 13x Solving 6 = 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 6 + -13x = 13x + -13x Combine like terms: 13x + -13x = 0 6 + -13x = 0 Add '-6' to each side of the equation. 6 + -6 + -13x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -13x = 0 + -6 -13x = 0 + -6 Combine like terms: 0 + -6 = -6 -13x = -6 Divide each side by '-13'. x = 0.4615384615 Simplifying x = 0.4615384615
| 12x-2(4x-9)=46 | | x+5=-3x+10 | | 2x-11y=-3 | | 4y-2=-23-3y | | -2x+7=-4+12 | | =2a(4a^2-6a+8) | | 2x+9=51 | | -4j^7(-9j^6)= | | 3-2x=-4[4+5(2x-1)] | | 8t^2+6t-9=0 | | 3p+8=-16 | | 4t^2=-6t | | -8y+9=24 | | 5x=33x+9 | | 8t+17=2 | | 2a+6-a=10+a-4 | | 3=6b+21 | | 8(y-2)=-3(3) | | x-(33.125)=-5.27 | | =(3y^3+9y^2-11y+8)-(-4y^2+10y-6) | | x(33.125)=-5.27 | | 10x-2(4x-4)=24 | | 13-3h=-8+4h-7 | | 99=95-h | | 3x-8x+12=(3x-8x)+12 | | 99=94-h | | 75+5x=79+4x | | 3x+12-8x=3x-8x+12 | | 120=3x+15 | | 5y-6=y-6 | | 2y-6=-13-5y | | 3x+64=5x |